Dimensions of Body-Awareness and Depressed Mood and Anxiety. (June 2019) - Solano López, Ana Laura; Moore, Shirley
Interoception, the multidimensional ability to sense the physiological condition of the body, is a key mechanism in emotional processing. However, the relationships between interoceptive dimensions and depressed mood and anxiety have not been widely studied. The aim of this secondary analysis, correlational and cross-sectional study, was to determine the relationships among interoceptive accuracy, interoceptive sensibility, depressed mood, and anxiety in adults with hypertension. The sample consisted of 76 adults, predominately African American women. Correlational analysis showed that most participants had low levels of interoceptive accuracy and relatively high levels of interoceptive sensibility. Interoceptive sensibility was negatively associated with depressed mood and anxiety. Interoceptive accuracy and interoceptive sensibility were not associated between each other. Further examination of the dimensions of interoception is needed to better understand the mechanisms by which it is associated with emotions that are known to have an influence on health behaviors and quality of life.